O site cinematecaparaense.org e a preservação virtual do patrimônio audiovisual: uma cartografia de vivências cinematográficas - SILVA, Ramiro Quaresma da (Universidade Federal do Pará, 2018)
This project proposes a cartography of the estate of Pará (Brazil) movies for a rhizomatic and multidimensional view of this cinematography. The research is presented in three stages. At first, the cartography method (Deleuze / Guattari) with emphasis on cinema (Kastrup), reflecting on the institution Cinematheque as guardian of the cinematographic memory of a place (Le Goff and Ferro) and a review of the literature and from sources on memory the Para cinema. Then in the second and longest stage, an inventory of filmography held in the state of Pará from 1960 to the present day, identifying the most relevant filmmakers and movies, describing their methods and filmic production from applied interviews and questionnaires, diversity theme of his scripts, developing an analysis of these works by identifying the historical, social, cultural and technological moments. Finally, the third stage, a reflection on the actions for the preservation of film archives in the state, the dilemma of contemporary cinema files, analog versus digital and Cinematheque of Pará site experience in preservation, cataloging and dissemination of virtual cinematography in cyberspace.